General Strain Theory for LGBQ and SSB Youth: The Importance of Intersectionality in the Future of Feminist Criminology. (October 2014) - Button, Deeanna M.; Worthen, Meredith G. F.
This study applies an intersectional general strain theory (GST) framework to understand the experiences of lesbian, gay, bisexual, questioning (LGBQ) youth, and youth involved in same-sex sexual behavior (SSB). Using a statewide probability sample of LGBQ and SSB youth ( N = 539) in grades 9 to 12, results show that understanding LGBQ and SSB youths' experiences with victimization (feeling unsafe, threatened/injured, property stolen) and negative outcomes (poor academic performance, substance use, suicidality) must be underscored with the significance of and intersections between gender, sexual identity, and sexual behavior. Implications for the importance of intersectionality in GST and the future of feminist criminology are offered.